Nama samaran/singkatan penulis Melayu abad 20: Senarai tambahan - Ding, C.M. (Perpustakaan Universiti Malaya, 1984)
Establishing Malay names for cataloguing or bibliograhic purposes has always posed a problem because of authors inclination to use varied pseudonyms which they may change in accordance to the kind of creative work. This problem is compouned by variant. form of spelling of names. To overcome these problems a ready list of Malay pseudonyms, together with authors' real names obtained from various sources between 7980-7983 would provide an "important reference tool. Such a list is provided below.